Utilization of Bagasse Ash to Reduce The Use of Cement in Brick Making - Rizki Angelina Naibaho; Ainun Rohana; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Need bricks for building materials is increasing, causing a reduction of agricultural land. One of the alternative to face this problem is the use of concrete block with a main components of cement, sand, water and other ingredients are added such ash baggase ash to reduce the use of cement. The purpose of this research was to reduce  the use of partial cement with bagasse ash in brick making toward compresssive strength and water absorption. The parameter of this research was compressive strenght, water absorption, brick size and analysis of production costs. Based on this research, it obtained that the compressive strength  of A1 was 2.146 Mpa, A2 was 2.836, A3 was 5.167. For  water absorption obtained result for A1 was 9.77%, A2 was 9.78 %, A3 was 16.05%. Brick size in this research have the same length and width for each treatment, while hight brick for A1 was 16.7 cm, A2 was 17.6 cm, A3 was 15.6 cm. The analysis of the cost of decreased production costs, A1 was 14.47%, A2 was 23.48%, A3 was 32.48%. Keywords : bagasse ash, brick